2018
DOI: 10.1155/2018/5949042
|View full text |Cite
|
Sign up to set email alerts
|

Cymbopogon citratusand NaNO2Behaviours in 3.5% NaCl-Immersed Steel-Reinforced Concrete: Implications for Eco-Friendly Corrosion Inhibitor Applications for Steel in Concrete

Abstract: This paper studies behaviours of Cymbopogon citratus leaf-extract and NaNO 2 , used as equal-mass admixture models, in 3.5% NaCl-immersed steel-reinforced concrete by nondestructive electrochemical methods and by compressive-strength improvement/reduction effects. Corrosion-rate, corrosion-current, and corrosion-potential constitute electrochemical test-techniques while compressive-strength effect investigations followed ASTM C29 and ASTM C33, in experiments using positive-controls for the electrochemical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…Cymbopogon citratus leaf extract inhibition efficiency is verified by Okeniyi et al [54] on NaCl-immersed concrete reinforced with carbon steel rebars. It is found that a leaf extract concentration of 0.083% vs. cement weight is sufficient to guarantee an IE% equal to 99.35%.…”
Section: Tests In Concretementioning
confidence: 78%
See 1 more Smart Citation
“…Cymbopogon citratus leaf extract inhibition efficiency is verified by Okeniyi et al [54] on NaCl-immersed concrete reinforced with carbon steel rebars. It is found that a leaf extract concentration of 0.083% vs. cement weight is sufficient to guarantee an IE% equal to 99.35%.…”
Section: Tests In Concretementioning
confidence: 78%
“…Another plant extract of interest is the one obtained from Cymbopogon citratus, a grass widely known and cultivated in Asia and India. A content of 0.083% vs. cement weight inside mortars gives an efficiency of 99.35%-beyond the inhibitive properties obtained by using 0.417% of NaNO 2 -also having beneficial effects on the mechanical properties of the tested concrete samples [54]. An interesting comparison between a green inhibitor and nitrites was offered by [46], who evaluated the effectiveness of licorice.…”
Section: Discussion and Comparison With Nitritesmentioning
confidence: 99%
“…h) Fresh leaves of Bambusa Arundinacea are used as corrosion mitigators in reinforced concrete when its ecofriendly, non-toxic and hydrophobic extract is added in concrete during casting [29]. i) A tropical plant, Cymbopogon citratus or lemon grass extract is superior than sodium nitrite in inhibiting corrosion [30]. A minor quantity of its extract is enough to add compressive strength and corrosion inhibition efficiency of RC.…”
Section: Figure 8 Schematic Representation Of Inhibitive Action Of Plant Extractmentioning
confidence: 99%
“…Due to the chloride attack, acid or sulphate attack, degradation of reinforcement in concrete occur which leads to the breakdown of the passivation film surrounding the reinforcement and makes the steel vulnerable to corrosion. Corrosion due to chloride attack on steel reinforcement bars in concrete is more dangerous because chloride ion promotes and accelerates the corrosion reaction by forming an intermediate product but without the chloride ion being consumed through the reaction process (Okeniyi et al 2018). Contaminated water, aggregate and admixtures containing chlorides are some of the ways the chlorides get into the fresh concrete.…”
Section: Introductionmentioning
confidence: 99%